2007
DOI: 10.1007/s10578-007-0082-5
|View full text |Cite
|
Sign up to set email alerts
|

Somatic Complaints in Children with Anxiety Disorders and their Unique Prediction of Poorer Academic Performance

Abstract: The present study aimed to examine somatic complaints in children with anxiety disorders compared to non-anxious control children and whether somatic complaints predict poorer academic performance. The sample consisted of 108 children and adolescents (aged 8-14 years) assessed by a structured diagnostic interview: 69 with a principal (i.e., most severe and/or interfering) anxiety disorder diagnosis and 39 non-anxious community controls. Established child and parent report measure of somatic complaints, anxiety… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
49
0
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 73 publications
(50 citation statements)
references
References 34 publications
0
49
0
1
Order By: Relevance
“…In a study, children with constipation and healthy controls were evaluated using the Behavior Rating Scale for Children and Young People, and the anxiety/depression subscale and total score was found significantly higher (14). It is reported that anxiety and depressive disorders accompanying somatic symptoms cause problems in school performance and may lead to school refusal, thereby decreasing the school achievement regardless of psychiatric disorders (21). Therefore, early diagnosis and regulation of the treatment is important.…”
Section: Discussionmentioning
confidence: 99%
“…In a study, children with constipation and healthy controls were evaluated using the Behavior Rating Scale for Children and Young People, and the anxiety/depression subscale and total score was found significantly higher (14). It is reported that anxiety and depressive disorders accompanying somatic symptoms cause problems in school performance and may lead to school refusal, thereby decreasing the school achievement regardless of psychiatric disorders (21). Therefore, early diagnosis and regulation of the treatment is important.…”
Section: Discussionmentioning
confidence: 99%
“…Rates of these disorders increase across time with roughly 25 % of adolescents suffering from an anxiety disorder and 10 % suffering from a mood disorder in the past year (Kessler et al 2012), and early onset is associated with more intractable course and poorer outcomes over time (Hammen et al 2008; Luby et al 2009; Ramsawh et al 2011), underscoring the critical need for effective early intervention. When left untreated, anxiety and depressive symptoms in youth are typically associated with disruptions in family functioning, school attendance, academic performance, and social relationships (Grills and Ollendick 2002; Hopkins et al 2013; Hughes et al 2008; Katz et al 2011). Younger children with early-onset anxiety and depression are particularly vulnerable given the potential for symptom impairments to interfere with a healthy developmental trajectory.…”
mentioning
confidence: 99%
“…Researchers found that depressive symptoms affected subsequent academic achievement with the possibility of a mediating third variable (Hishinuma, Chang, McArdle, & Hamagami, 2012). Another group of researchers showed that children with anxiety disorders reported more somatic complaints than did the non-anxious children, and the higher frequency of somatic complaints specifically predicted poorer academic performance (Hughes, Lourea-Waddell, & Kendall, 2008). Attention problems also predict academic problems such as grade repetition and lower scores on achievement tests (Polderman, Boomsma, Bartels, Verhulst, & Huizink, 2010).…”
Section: Prediction Effects Of Problem Behaviors On Academic Achievementmentioning
confidence: 99%